Dedifferentiation of tobacco cells is associated with ribosomal RNA gene hypomethylation, increased transcription, and chromatin alterations - Koukalova, Blazena; Fojtova, Miloslava; Lim, Kar Yoong; Fulnecek, Jaroslav; Leitch, Andrew Rowland; Kovarik, Ales (Plant physiology, 2005)
Epigenetic changes accompanying plant cell dedifferentiation and differentiation are reported in 35S ribosomal DNA (rDNA) of tobacco (Nicotiana tabacum). There was a reduction of CG and CNG methylation in both intergenic and genic regions of the rDNA cistron in fully dedifferentiated callus and root compared to leaf. The rDNA hypomethylation was not random, but targeted to particular rDNA gene families at units that are clustered within the tandem array. The process of hypomethylation was initiated as early as 2 weeks after the callus induction and established epigenetic patterns were stably maintained throughout prolonged culture. However, regenerated plants and their progeny showed partial and complete remethylation of units, respectively. Nuclear run-on assays revealed a 2-fold increase of primary (unprocessed) ribosomal RNA transcripts in callus compared to leaf tissue. However, the abundance of mature transcripts in callus was elevated by only about 25%. Fluorescence in situ hybridization analysis of interphase nuclei showed high levels of rDNA chromatin condensation in both callus and leaf, with substantially less decondensed rDNA than is observed in meristematic root-tip cells. It is likely that the regions of the rDNA locus showing decondensation correspond to the clusters of hypomethylated units that occur in the tandem array at each locus. The data together indicate that the establishment of pluripotency and cell proliferation occurring with callus induction is associated with enhanced ribosomal RNA gene expression and overall rDNA hypomethylation, but is not associated with material-enhanced relaxation of chromatin structure (decondensation) at rDNA loci.
Keywords: RNA, Ribosomal; regenerace; Plant Leaves; Cells, Cultured; hybridizace in situ fluorescenční; Cell Differentiation; Chromatin; RNA ribozomální; DNA Methylation; In Situ Hybridization, Fluorescence; Nicotiana; messenger RNA; metylace DNA; Interphase; Transcription, Genetic; Gene Expression Regulation, Plant; listy rostlin; Plant Roots; kultivované buňky; tabák; chromatin; kořeny rostlin; RNA, Messenger; regulace genové exprese u rostlin; Regeneration; interfáze; buněčná diferenciace; genetická transkripce